LINC00035 Transcriptional Regulation of SLC16A3 via CEBPB Affects Glycolysis and Cell Apoptosis in Ovarian Cancer. (11th October 2021) - Yang, Shuyan; Wang, Jing; Cheng, Rongjie; Pang, Bo; Sun, Pengcheng
Abstract : Objective . Ovarian cancer (OC) represents the most lethal gynecologic malignancy globally. Over the decades, lncRNAs have been considered as study focuses due to their genome-wide expression through multiple mechanisms in which regulation of target gene transcription through interaction with transcription factors or epigenetic proteins is proven. In the present work, we focus on the functional role of LINC00035 in OC and its regulation mechanism on gene expression. Methods . We collected OC tissues and adjacent tumor-free tissues surgically resected from 67 OC patients. Cultured human OC cell lines SKOV3 and A2780 were assayed for their viability, migration, invasion, apoptosis in vitro using CCK-8 assays, transwell assays, and flow cytometric analysis. OC cell tumorigenesis in vivo was evaluated by mouse xenograft experiments. Glycolysis was evaluated by glucose uptake, lactate release, and ATP production assays. Luciferase activity assay, RNA immunoprecipitation (RIP), and RNA pull-down were performed to confirm the interactions among LINC00035, CEBPB, and SLC16A3. Results . LINC00035 was upregulated in OC tissues. LINC00035 knockdown was shown to repress SKOV3 and A2780 cell viability, migration, invasion, induce their apoptosis, and reduce glucose uptake, lactate release, and ATP production. LINC00035 could recruit CEBPB into the SLC16A3 promoter region, thus increasing the SLC16A3 transcription. SLC16A3 was upregulated in OC tissues. SLC16A3 knockdown exerted similar effects on SKOV3 and A2780 cells as LINC00035 knockdown. Rescue experiments found SLC16A3 overexpression resisting to LINC00035 knockdown on SKOV3 and A2780 cell viability, migration, invasion, apoptosis, glucose uptake, lactate release, and ATP production. Results also showed LINC00035 knockdown could inhibit OC cell tumorigenesis in vivo . Conclusion . The study reveals that LINC00035 promotes OC progression by regulating glycolysis and cell apoptosis through CEBPB-mediated transcriptional promotion of SLC16A3.